Chloroquine-primaquine therapeutic response and safety in patients with uncomplicated Plasmodium vivax malaria in the Colombian Amazon region - Paula Calderón-Ruiz; Gabriel Velez-Tobón; Sebastian Bolívar-Hernández; Luz Mila Murcia-Montaño; Alberto Tobón-Castaño (Malaria Journal)
Abstract Background In Colombia, published studies on the treatment of uncomplicated Plasmodium vivax malaria with chloroquine-primaquine are scarce. The aim of this study was to evaluate the therapeutic response to two treatment regimens at the 28-day follow-up and the occurrence of adverse events in patients with P. vivax malaria. Methods A quasi-experimental clinical trial was conducted at 3 sites in the Department of Amazonas. Patients received supervised or unsupervised anti-malarial treatment (chloroquine plus primaquine), and the primary effectiveness endpoint was the clinical and parasitological response. Safety was assessed through adverse event surveillance. Results A total of 103 patients were included: 53 in the 7-day primaquine group (Group I) and 50 in the group receiving primaquine for 14 days (Group II). Among the patients in group I, an adequate treatment response of 100% and 89.5% was found in patients who received supervised and unsupervised treatment, respectively. In Group II, adequate responses of 100% and 95% were reported for patients who received supervised and unsupervised treatment, respectively. No adverse events were detected. Conclusions The response to combined treatment with chloroquine plus primaquine continues to be adequate for treating P. vivax malaria in the Colombian Amazon region; however, a response to unsupervised treatment in the region is recommended.